In Vitro Antibacterial Activity of Selected Palestinian Medicinal Plants against Chlamydia trachomatis - Omar Hamarsheh; Ahmad Amro; Munir A. Al-Zeer (Microbiology Research, 2021)
Chlamydia spp. are intracellular pathogens of humans and animals that cause a wide range of diseases such as blinding trachoma and sexually transmitted infections. According to the World Health Organization (WHO), there are more than 127 million new infections each year worldwide. Chlamydial urogenital infections can cause cervicitis, urethritis, pelvic inflammatory disease and infertility. From within an intracellular niche, termed an inclusion, the Chlamydiae complete their life cycle shielded from host defenses. The host cell defense response used to eliminate the pathogen must subvert this protective shield and is thought to involve the gamma interferon-inducible family of immunity related GTPase proteins and nitric oxide. Typically, azithromycin and doxycycline are the first line drugs for the treatment of chlamydial infections. Although C. trachomatis is sensitive to these antibiotics in vitro, currently, there is increasing bacterial resistance to antibiotics including multidrug-resistant C. trachomatis, which have been described in many instances. Therefore, alternative drug candidates against Chlamydia should be assessed in vitro. In this study, we tested and quantified the activity of plant extracts against Chlamydia-infected HeLa cells with C. trachomatis inclusions. The in vitro results show that post-treatment with Artemisia inculta Delile extract significantly inhibits Chlamydia infection compared to DMSO-treated samples. In conclusion, plant extracts may contain active ingredients with antichlamydial activity potential and can be used as alternative drug candidates for treatment of Chlamydia infection which has significant socio-economic and medical impact.